Squamous Odontogenic Tumor with Unusual Localization and Appearance: A Rare Case Report - Sucheta Bansal; Sanjeev Kumar Joshi (Case Reports in Medicine)
Squamous odontogenic tumor is a rare benign neoplasm and may affect multiple sites in the mouth. SOT was first described by Pullon et al. (1975). Since then, there have been less than 50 reported cases. The tumor is often asymptomatic, although it can present with symptoms of pain and tooth mobility. We report a case of SOT occurring in a 26-year-old female in the anterior mandible with unusual localization and appearance.